PENNGELOLAAN SAMPAH DI PASAR ALAI KELURAHAN ALAI PARAK KOPI KECAMATAN PADANG UTARA - Ramadhani, Hilda; Drs. Dasrizal, MP, Drs. Dasrizal, MP; Erita, Yeni (STKIP PGRI Sumbar, 2014)
ABSTRACT The purposes of this research are to collect, process, analyze and discuss data about trash management in Alai Market, district of Alai Parak Kopi, subdistrict of North Padang. This research is include in descriptive research is include in descriptive research. The population for this research is all of the sellers in Alai Market. Sample of the research is taken with Proportional Random Sampling technique, by the proportion 25% taken from the population of research area totally 97 sellers in Alai Market. Based on the used analysis as descriptive statistic by using percentage formula. Result of the research shows: 1) The condition of basic and pre-basic for the trash management, generally facilitate the trash cans (98,96%) and the government also facilitates trash bins (97,93%), meanwhile the pre-basic of trash management is trash pick-up car (97,93%), the ways in Alai Market are ground (43,29%), the transportation in the market is available (81,44%) 2) The understanding of sellers about the trash management in Alai market, generally they have known the meaning of clean environment and trash management (58,76%) and responsibility of the trash management and keeping the environment clean are handled by all of the sellers there (96,90%) 3) The act and function of government for the trash management in Alai market, generally facilitates infrastructur (91,75%), there is the last bin for market trash (91,75%), and there are two workers available in Alai market (53,60%).